Determining the tropopause height from 205 MHz stratosphere troposphere wind profiler radar and study the factors affecting its variability during monsoon. (January 2019) - Nithya, K.; Kottayil, Ajil; Mohanakumar, K.
Abstract: A Stratosphere-Troposphere (ST) wind profiler radar at 205 MHz is operational at Cochin (10.04 N; 76.44 E), India since January 2017 and is providing accurate three-dimensional wind profiles for an altitude range of 315 m to 20 km. In this paper, we present a method to estimate the tropopause altitude from signal to noise ratio (SNR) profiles obtained from the 205 MHz wind profiler radar. The gradient in SNR is used to estimate the cold point tropopause (CPT) height. The CPT height obtained from the ST radar is validated against co-located radiosonde tropopause height measurements and is found to be in very good agreement. The variability of CPT height during monsoon season was studied and the factors responsible for its variability were investigated. It is found that during monsoon season the Tropical Easterly Jet (TEJ) has an inverse relationship with the CPT height, i.e. CPT height increases as the strength of TEJ diminishes and vice versa. A comparison between TEJ core speed and ice cloud water path (ICWP) which represents the strength of deep convection, shows that ICWP decreases as the strength of TEJ increases. Thus, our analysis shows that TEJ affects the tropopause height through changing the concentration of ice clouds. Highlights: Cold point tropopause height from 205 MHz wind profiler radar. Variability of tropopause height during south west monsoon season over Cochin. Association between tropical easterly jet core speed and cold point tropopause height.